Connecting heart failure with preserved ejection fraction and renal dysfunction: the role of endothelial dysfunction and inflammation. (10th February 2016) - ter Maaten, Jozine M.; Damman, Kevin; Verhaar, Marianne C.; Paulus, Walter J.; Duncker, Dirk J.; Cheng, Caroline; van Heerebeek, Loek; Hillege, Hans L.; Lam, Carolyn S.P.; Navis, Gerjan; Voors, Adriaan A.
Abstract : Renal dysfunction in heart failure with preserved ejection fraction (HFpEF) is common and is associated with increased mortality. Impaired renal function is also a risk factor for developing HFpEF. A new paradigm for HFpEF, proposing a sequence of events leading to myocardial remodelling and dysfunction in HFpEF, was recently introduced, involving inflammatory, microvascular, and cardiac components. The kidney might play a key role in this systemic process. Renal impairment causes metabolic and systemic derangements in circulating factors, causing an activated systemic inflammatory state and endothelial dysfunction, which may lead to cardiomyocyte stiffening, hypertrophy, and interstitial fibrosis via cross‐talk between the endothelium and cardiomyocyte compartments. Here, we review the role of endothelial dysfunction and inflammation to explain the link between renal dysfunction and HFpEF, which allows for identification of new early risk markers, prognostic factors, and unique targets for intervention.